2016
DOI: 10.1111/jfb.12920
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive parameters of the Pacific angel shark Squatina californica (Selachii: Squatinidae)

Abstract: Reproductive characteristics of the Pacific angel shark, Squatina californica, were evaluated from 420 specimens obtained from the artisanal fishery in La Paz Bay, Gulf of California, Mexico. Females (99 cm, 6000 g) were larger than males (95 cm, 5000 g) in terms of both total length (L(T)) and body mass (M(T)). The overall sex ratio was significantly different from the expected 1:1, suggesting sexual segregation of mature individuals in La Paz Bay. Males had developed reproductive organs and calcified clasper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
(56 reference statements)
2
5
0
1
Order By: Relevance
“…The regional genetic variation observed in our study could be linked to ontogenetic differences in S. californica between study areas. Length at sexual maturity (LSM) and maximum total length (MTL) are lower in individuals from the gulf area (LSM = 70.0-77.7 cm; MTL = 88-99 cm) than in individuals from the Pacific area (LSM = 99 cm; MTL = 117 cm) (Villavicencio-Garayzar 1996, Romero-Caicedo et al 2016. Morphological differences and genetic differentiation are both in agreement with the population structure of this species in the study area.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The regional genetic variation observed in our study could be linked to ontogenetic differences in S. californica between study areas. Length at sexual maturity (LSM) and maximum total length (MTL) are lower in individuals from the gulf area (LSM = 70.0-77.7 cm; MTL = 88-99 cm) than in individuals from the Pacific area (LSM = 99 cm; MTL = 117 cm) (Villavicencio-Garayzar 1996, Romero-Caicedo et al 2016. Morphological differences and genetic differentiation are both in agreement with the population structure of this species in the study area.…”
Section: Discussionsupporting
confidence: 66%
“…Taking into account the characteristics of S. californica, we consider that the submarine canyons constitute a natural barrier for its dispersal. Geomorphology off northwestern Mexico is complex, and there are numerous submarine canyons and great depths (at the mouth of the Gulf of California, the ocean basin drops to over 3,000 m) (Gutiérrez et al (Villavicencio-Garayzar 1996, Romero-Caicedo et al 2016. Las diferencias tanto morfológicas como genéticas concuerdan con la estructura poblacional de esta especie en el área de estudio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biological information about the Pacific angel shark in Mexico is fragmented and limited to a few studies on trophic ecology and reproduction (Escobar-Sánchez et al, 2006Romero-Caicedo et al, 2016). Using mitochondrial DNA, Ramírez-Amaro et al (2017) reported genetic differences between specimens from the GOC and Pacific coast of the BCP, validating previous observations of life history differences between specimens from these areas (Villavicencio-Garayzar, 1996). Similarly, Márquez-Farías (2007) found maximum lengths and lengths at maturity for the population of shovelnose guitarfish (Pseudobatus productus) in the GOC that are different from those reported for the population along the Pacific coast of the BCP (Villavicencio-Garayzar, 1995).…”
supporting
confidence: 85%